Bird Diet in Oil Palm Plantation and the Secondary Forest in Bau, Sarawak - Siti Noor Syafiqah, Ismail (Universiti Malaysia Sarawak (UNIMAS), 2015)
Few study on the diet of birds been done in Sarawak, and habitat fragmentation had been causing the alteration of diet of birds. The diet of birds in two different habitats (secondary forest, and oil palm plantation) were investigated in Salcra - Jagoi Estate Oil Palm Plantation located in Bau, Sarawak, Malaysia. Mist-netting method was used to capture the birds. Two methods of analysing diet of birds were used; faecal collection and stomach content analysis. A total of 13 species of birds from 7 families were recorded in the 2 habitats. The diet of the birds contains Coleoptera (46.67%), Hymenoptera (20.0%), Orthoptera (14.67%), Odonata (6.67%), Diptera (5.33%), unidentified order (4.0%) and Hemiptera (2.67%). The relative abundance of insect at the oil palm area was higher than in the secondary forest. The vegetation structure and condition determines the insect and bird occurrence. In addition, the size of the bird was correlated with the size of their insect prey.